Male and Female’s Speaking Abilities Differences in Debating Context (Indo-MathEdu Intellectuals Journal, 2023)
This study analyzed the differences in male and female speaking skills such as organization, opinion, rebuttal, sentence structure, and fluency in debate activities. This study used descriptive-qualitative methods and collected the data by using observations, audiovisual recordings, and interviews. As a result, male students were better than female students in constructing speeches, presenting their arguments, responding to opponents, organizing sentences, lexical hedges, and intensifiers in their sentences, and speaking their own words fluently. They could understand the main points, rephrase sentences, use reinforcing words, and sometimes produce pauses. On the contrary, female students were unsuccessful in delivering the main points, using unfinished sentences, repeating the sentences, using lexical hedges and intensifiers, and producing frequent pauses in debate activities. Thus, teachers should use different methods in teaching, assessing, and measuring the speaking ability of male and female students in debate activities, particularly in Speaking classes.